Liberal democracy, competition, and the institutional limits of markets - Agmon, S (2023)
This thesis addresses a particular class of problems affecting liberal democracies worldwide, namely, that some of their most central institutions—the electoral system, the legal system, and the free press—are undermined by their partial or complete subordination to the market. I provide a comprehensive normative analysis of this class of problems and answer the following questions: is it justifiable to place limits on markets in certain institutional goods (e.g., legal representation and the reporting of news), and if so, what should those limits be?